Quality of Life and Specific Difficulties of Children with Autism Spectrum Disorder Among Saudi Primary Caregivers - Hanan Abd Elwahab Elsayed; Sultan Ahmed Alanazi; Manal Saleh Moustafa Saleh (Healthcare, 2026)
Background: The prevalence of autism spectrum disorder (ASD) is increasing globally and in Saudi Arabia (SA), although many cases remain undiagnosed. Caregivers of children with ASD are confronted by challenges, especially mothers as primary caregivers, who have higher levels of stress and burden of care due to autism symptoms and difficulties of children, which negatively affects their quality of life (QoL). Objective: The primary outcome of this study was to assess primary caregivers’ quality of life and their perceptions of child-related difficulties associated with autism spectrum disorder (ASD) using the Quality of Life in Autism (QoLA) questionnaire. The secondary outcome was to examine the correlation between these two QoLA domains and identify the factors independently associated with each outcome Material and Methods: A convenience sample (247) of Saudi primary caregivers, primarily mothers, was taken from autism primary schools in Tabuk, Riyadh, Qassim, Hail, Jazan & Najran cities in SA by distributing an online questionnaire, which was composed of three parts, was used for data collection; Part I included demographic and clinical data of primary caregivers. Part II: The child’s personal characteristics. Part III: QoLA Questionnaire that measures the crucial aspects of living with autistic children and is composed of two parts (A and B). Data analysis was performed using the Statistical Package for the Social Sciences (SPSS Inc., Chicago, IL, USA), version 23. Results: More than half of the caregivers (50.2%) had a moderate level of QoL. Regarding caregivers’ perceptions of child-related difficulties, 70.9% reported high levels of difficulties, and 7.2% reported low difficulties. Quality of life was significantly associated with maternal age, educational level, number of children. The study’s univariate regression and multivariate regression analysis revealed that, QoL score had a significant negative association with maternal ages, university school and secondary school, working, and those who had medical diseases. In contrast, QoL level had a significant positive association with mothers who received training, had another person helped in caring for the child and who had enough income. Conclusions: Mothers of autistic children had poorer QOL and perceived more difficulties in caring for their children. Thus, educating sessions for mothers about dealing with their autistic children, psychological and financial support services are needed, which in turn improve their QoL.